Freedom of Religion and Religious Relations (Construction of Sukarno's Thought) - Muhammad Salahuddin; Muhammad Sabri (Badan Pembinaan Ideologi Pancasila, 2022)
The question of religious connections is constantly linked to the concept of religious freedom, which is a basic human right. This understanding of religion and religiousity must be maintained in order to obtain a tolerance attitude among religious groups. This is essential in development because religion and God are vital to human activity. The principles of the Oneness of God in the Pancasila s state foundation are the result of the Indonesian national figures thought about the problems raised above. The final dialogue of the Indonesian nation's founding fathers is the oneness og God as the foundation of all other of Panscasila principles. This article further elaborates on Sukarno's concept of divinity by combining the concepts of perennial philosophy, systems theory, and paradigm shift, which are related to the context of religious life in Indonesia.